Caracterização e evolução de parálogos de CenH3 em espécies de Drosophila do grupo repleta - Erick Weberth de Lima Junqueira (2019)
Centromeres are important regions for chromosome segregation, with satellite DNAs and transposable elements being their most abundant components. During the cell division, the centromeric protein CenH3, which is a variant of histone H3, interacts with the centromeric DNA forming a specific nucleosome in the centromere. Both, centromeric DNA and centromeric proteins, have a rapid evolution rate, which is an unexpected fact considering the important role of the centromere. According to the centromere drive hypothesis, the expansion of centromeric DNA in a specific chromosome implies in increase recruitment of centromeric proteins, which ultimately favours preferential transmission of the chromosome to the egg and hence to the next generation. Disadvantages of this phenomenon include increased infertility in male and the possible increase in the frequency of chromosomes that may carry deleterious mutations. In Drosophila, the centromeric protein CenH3 is known as Cid, which previous studies have shown the existence of paralogs of this gene in species of the Drosophila subgenus. The present project aimed to broaden the studies of Cid paralogs in species from the repleta group, to determine the phylogenetic origin of Cid1-Cid6 gene duplication, to characterize all found paralogs and to test the possible existence of positive selection on them. For this, molecular biology techniques associated with bioinformatics analysis were used. The results indicate that the Cid6 paralog was already present in the common ancestor of the buzzatii complex. Only Cid1 and Cid5 paralogs were found in mojavensis cluster, whereas Cid6 and Cid5 were found in the buzzatii complex. Furthermore, our analysis indicates that Cid5, a paralog found in the Drosophila male, is under positive selection, suggesting that this paralog could act as a centromere drive suppressor in Drosophila species.